2013
DOI: 10.1093/pcp/pct061
|View full text |Cite
|
Sign up to set email alerts
|

The Plant S1-Like Nuclease Family Has Evolved a Highly Diverse Range of Catalytic Capabilities

Abstract: Plant S1-like nucleases, often referred to as nuclease I enzymes, are the main class of enzymes involved in nucleic acid degradation during plant programmed cell death. The catalytically active site of these enzymes shows a significant similarity to the well-described P1 nuclease from Penicillium citrinum. Previously published studies reported that plant S1-like nucleases possess catalytic activities similar to their fungal orthologs, i.e. they hydrolyze single-stranded DNA and RNA, and less efficiently double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…In conclusion, in cacao, the COC dissolution which occurred in both resistant and susceptible genotypes led to extracellular Ca 2+ availability that may be used by the TcPR-4b for its acting as DNase in resistance mechanisms or in PCD during the infection process. This may be reinforced by the fact that the calcium availability is higher in the apoplasm in normal cells, while an influx of calcium in the intracellular area occurred during PCD [63]. …”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, in cacao, the COC dissolution which occurred in both resistant and susceptible genotypes led to extracellular Ca 2+ availability that may be used by the TcPR-4b for its acting as DNase in resistance mechanisms or in PCD during the infection process. This may be reinforced by the fact that the calcium availability is higher in the apoplasm in normal cells, while an influx of calcium in the intracellular area occurred during PCD [63]. …”
Section: Discussionmentioning
confidence: 99%
“…Nuclease activity is associated with nuclear DNA fragmentation phenomena [34,53]. Plant S1-like nucleases, the main class of single-stranded specific nucleases (often termed as type I nucleases), degrade both RNA and ssDNA during plant PCD [54]. Here, we observed that the activity of neutral nucleases with molecular masses of approximately 38, 33 and 26 kDa was induced at early senescent stages.…”
Section: Discussionmentioning
confidence: 80%
“…Here, we observed that the activity of neutral nucleases with molecular masses of approximately 38, 33 and 26 kDa was induced at early senescent stages. BFN1 is a nuclease with a molecular mass of approximately 38 kDa which has been detected in Arabidopsis during leaf and stem senescence [54][55][56]. The specific function of BFN1 has not yet been demonstrated, but it has been suggested to be involved in the nucleic acid degradation that takes place during both senescence and developmental PCD [56].…”
Section: Discussionmentioning
confidence: 99%
“…Ac343 also presented 55% amino acid identity to the best characterized plant S1-like nucleases, ZEN1 of Zinnia elegans and Arabidopsis ENDO1 (also named bifunctional nuclease1, BFN1). Previous reports have demonstrated that BFN1 and ZEN1 are involved in different forms of PCD (Pérez-Amador et al, 2000; Ko et al, 2012; Lesniewicz et al, 2013). Finally, Ac114 revealed the presence of a conserved DNase-RNase domain, which is characteristic of a family of bifunctional nucleases having both DNase and RNase activity.…”
Section: Discussionmentioning
confidence: 99%